Accuracy of Apple Watch in Measuring 30-Second Resting Electrocardiography in Patients with Cardiac Diseases and Comorbidity: An Observational Cross-Sectional Study - Khushhal AA; Mohamed AA; Alsegame MM; Alsaedi AM (Journal of Multidisciplinary Healthcare)
Alaa Abdulhafiz Khushhal,1 Ashraf Abdelaal Mohamed,1 Mohammad Matook Alsegame,2 Atif Mohammed Alsaedi2 1Department of Medical Rehabilitation Sciences, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 2Department of Nursing, Umm Al-Qura University Medical Center, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Alaa Abdulhafiz Khushhal, Department of Medical Rehabilitation Sciences, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia, Tel +966536025182, Email aakhushhal@uqu.edu.saBackground: Electrocardiography (ECG) is a standard method for studying the heart rate and heart electricity. The Apple Watch has recently been used to measure heart electricity via 30 seconds of ECG monitoring, but its validity is not known.Methods: A cross-sectional study included a sample of 112 patients with chronic disorders, including cardiac patients with sinus rhythm, cardiac patients with irregular heart rhythm, and patients with diabetes, hypertension, and dyslipidemia; their cardiac activity was investigated using the Apple Watch and ECG.Results: The correlations were strong between the Apple Watch and the 12-lead ECG in the heart rate, PR intervals, QT intervals, QRS complex, and RR intervals in all patients’ subcategories (cardiac, hypertension, diabetic, and dyslipidemia patients).Conclusion: The Apple Watch is valid for carrying out ECG in measuring the heart rate, PR intervals, QT intervals, QRS complex, and RR intervals of patients with cardiac and chronic diseases at rest; this may help in initial diagnosis for patients with cardiac diseases or those who are at risk of developing cardiac disease in the future.Keywords: Apple Watch, electrocardiography, cardiac diseases, chronic diseases